Inflammatory Bowel Disease (IBD) and immunosuppression do not worsen the prognosis of COVID-19. Results from the ENEIDA Project of GETECCU. (27th May 2021) - Zabana Abdo, Y; Marín-Jiménez, I; Rodríguez-Lago, I; Ramírez Esteso, F; Meijilde, S; Ramos, L; Gomollón, F; Muñoz, F; Suris, G; Ortiz de Zárate, J; Huguet, J M; Llaó, J; et al.
Abstract: Background: The exhaustive registry of COVID-19 cases in patients with IBD is a unique opportunity to learn how to deal with this infection, especially in reference to the management of immunosuppressive treatment, isolation measures or if the disease is more severe in IBD patients due to immunosuppression. With these premises, the aims of this study were to know the incidence and characteristics of COVID-19 in the ENEIDA cohort during the first wave of the pandemic; the outcomes among those under immunosuppressants/biologics for IBD; the risk factors for contracting the infection and poor outcomes; and the impact of the infection after three-month follow-up. Methods: Prospective observational cohort study of all IBD patients with COVID-19 included in the ENEIDA registry (with 60.512 patients in that period) between March and July 2020, with at least 3 months of follow-up. Any patient with a confirmed (by PCR or SARS-CoV-2 serology) or probable (suggestive clinical picture) infection was considered as a case. Results: A total of 484 patients with COVID-19 from 63 centres were included: 247 Crohn's disease, 223 ulcerative colitis and 14 unclassified colitis; median age 52 years (IQR: 42–61), 48% women and 44% ≥1 comorbidity. Diagnosis was made by PCR: 63% and serology: 35%. The most frequent symptoms: fever (69%), followed by cough (63%) and asthenia (38%). During lockdown 78% followed strict isolation. 35% required hospital admission (ICU: 2.7%) and 12% fulfilled criteria for SIRS upon admission. 16 patients died from COVID-19 (mortality:3.3%). 12% stop IBD medication during COVID-19. At 3 months, taken into account all included cases, 76% were in remission of IBD. Male gender (OR 1.56; 95%CI:1–2.4, p=0.05), ≥40 years of age (OR 2.55; 95% CI:1.4–4.8; p=0.004), Charlson score ≥1 (OR 2.1; 95% CI:1.3–3.5; p=0.004), and systemic steroids <3 months before infection (OR 1.8; 95%CI:1–1.6; p= 0.032), were risk factors for hospitalisation due to COVID-19, while occupation considered of risk was actually protective (OR 0.58; 95%CI:0.3–0.99; p=0.046). A Charlson score ≥ 1 (OR 5.5; 95%CI:1.5–20.3; p=0.001) and the use of aminosalicylates at COVID-19 diagnosis (OR 4.6;95%CI:1.2–17; p=0.023) were associated with ICU admission. Age ≥60 years (OR 6.5; 95%CI:1.7–25.5; p=0.007) was the only risk factor for COVID-19 related death. Conclusion: IBD does not seem to worsen the prognosis of COVID-19, even when immunosuppressants and biological drugs are used. Age and comorbidity are the most important prognostic factors for more severe COVID-19 in IBD patients. The use of aminosalicylates and the risk of a worse outcome deserves a deeper analysis. Funded by the Carlos III Health Institute (COV20 / 00227).